The Analysis of operational efficiency and service quality: Case of the South Valdivia Day Hospital, Guayaquil – Ecuador. - Monteros Castillo, Ericka Lorena; Núñez Alvarez, Ana Mercedes; Hernández Ludeña, Karen Carolina (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This study analyzes the relationship between operational efficiency and service quality at the Valdivia South Day Hospital, located in Guayaquil, Ecuador. The research stems from the problem that public hospitals face budgetary constraints, high demand, and complex regulatory frameworks, making it difficult to guarantee efficient and high-quality services. In this context, the objective was to determine if a significant relationship exists between operational efficiency and service quality at this institution. A quantitative approach with a non-experimental, retrospective longitudinal design was used. The research was based on 72 monthly observations from 2019–2024, obtained from institutional records of the Results-Based Management (RBM) system. Service quality was measured using an index that integrates continuity of care, compliance with standards, and operational results, while operational efficiency was evaluated using indicators related to resource management and internal processes. The results show a negative correlation between operational efficiency and service quality (r ≈ -0.31). The linear regression model indicates that increases in efficiency are associated with reductions in quality (β = -0.486), although the model's explanatory power is limited (R² = 0.097). In conclusion, the findings suggest a trade-off between efficiency and quality, implying that strategies focused solely on improving productivity could negatively impact certain aspects of service quality. It is recommended that multiple organizational factors be considered to achieve a balance between these two dimensions.